The Effect Of Obstacle Jumping Practice And Jumping Up Practice On Smash Skills In Volleyball Games - Sahabuddin, Sahabuddin; Ishak, Muhammad (Journal of Sport Education, Coaching, and Health (JOCCA), 2024)
This study is a field experiment research that aims to determine the difference in the influence between obstacle jumping and jumping up training on smash skills in volleyball games in students of SMA Negeri 6 Makassar. The population is male students of SMA Negeri 6 Makassar with a sample of 60 people. The data analysis technique is a t-test at a significant level of 95%. The results of the obtained values show that: There is a significant influence between obstacle jumping practice on smash skills in volleyball games (to = 23.453 > tt = 2.045). There is a significant influence of jump-up practice on smash skills in the game of volleyball (to = 14,765 > tt = 2,045). There was a significant difference in influence between obstacle jumping training and up jumping training on smash skills in volleyball games (to=10,522 > tt=2,000), and obstacle jumping training was better than obstacle jumping training.